m-13=37

Simple and best practice solution for m-13=37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-13=37 equation:


Simplifying
m + -13 = 37

Reorder the terms:
-13 + m = 37

Solving
-13 + m = 37

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + m = 37 + 13

Combine like terms: -13 + 13 = 0
0 + m = 37 + 13
m = 37 + 13

Combine like terms: 37 + 13 = 50
m = 50

Simplifying
m = 50

See similar equations:

| 25-6b=55 | | 2k-5=3(1-2k) | | 4(c+2)=-28 | | a+5=3a+13 | | -z+7=-8 | | 3(8-2n)=3n+6-9n | | 2s+5=14+s | | -12x+3=-9 | | 3x^2=64 | | 20=6+2d | | 10y-200=350 | | X-8-9=-5 | | 5x^3-31x^2+11x-1=0 | | 3x^2+(X+2)=64 | | -60-2x=24 | | 40=-4(3n+2) | | (4+5x)+3= | | a=101+-14.2 | | 2X(5+3)=80 | | 7a+4b=64 | | 3(8-2n)=3n+6-9n-4 | | 3x^2X+8=80 | | 4a+7b=64 | | 27=15x-3 | | 4a+7a=64 | | 5r+4-8=16 | | 7X+(5-2)=38 | | x^2+x-2=0 | | t+9=3t-5 | | 11x-(-24)=57 | | 4(x-2)-(x-8)=18 | | 8a-3a=-15 |

Equations solver categories